A Message from the Editor-in-Chief - Jankauskas, Rimantas (Acta medica Lituanica, 2020)
A Message from the Editor-in-Chief This issue of Acta medica Lituanica is the result of further evolution: from now on, our journal is being published by the Vilnius University Press. Probably you noted changed design, but most changes are within the system of submission and publishing. All they serve the main goal – wider and more effective dissemination of knowledge. Vilnius University Press is the academic community owned publishing platform – it means that academics play a key role in dissemination of results of their research. This enables also more effective implementation of academic freedom, more innovations, more transparency. Finally, it also means more Open Science. Publications in our journal are and will be freely accessible and free of article processing charges. This is already the second issue that was formed at the time of extreme challenges for biomedical community due to the global COVID-19 pandemic. Many of us found ourselves at the frontline dealing with this critical situation and fulfilling our duty to society. This issue starts with a review paper dedicated to the problem No.1; some more are under review. Another paper is dealing with professional burnout – not a minor problem for health professionals nowadays. Other research papers and case studies remind us about life before and (let’s hope) after the pandemic. Finally, I want to thank our reviewers who sacrificed their time evaluating manuscripts: Sigita Aidietienė Vidmantas Alekna Karolis Ažukaitis Valdas Banys Aušra Beržanskytė Žana Bumbulienė Jolanta Dadonienė Gytė Damulevičienė Edvardas Danila Audrius Dulskas Milda Endzinienė Eglė Ereminienė Žymantas Jagelavičius Ligita Jančorienė Ričardas Janilionis Augustina Jankauskienė Dalius Jatužis Tomas Kačergius Vytautas Kasiulevičius Jacek Kubica Vaidutis Kučinskas Zita Kučinskienė Limas Kupčinskas Sigita Lesinskienė Mieczyslaw Litwin Rūta Mameniškienė Rūta Nadišauskienė Alvydas Navickas Janina Petkevičienė Narūnas Porvaneckas Tomas Poškus Dainius Pūras Rūta Sargautytė Jūratė Šipylaitė Povilas Sladkevičius Eugenijus Stratilatovas Arūnas Strumila Rasa Strupaitė-Šileikienė Virgilijus Tarutis Vytautas Tutkus Albertas Ulys Vincas Urbonas Algirdas Utkus Birutė Vaišnytė Respectfully, Prof. Dr Rimantas Jankauskas, Editor-in-Chief Acta medica Lituanica